Conflicting notions of language in metalinguistic discourses in Lithuania, Norway and Serbia - Vukotić, Vuk (Taikomoji kalbotyra, 2014)
The article analyses the notions of language and their elements in metalinguistic comments taken from comment sections in online news portals from Lithuania, Norway and Serbia. The aim is to find and categorize different types of language notions. The goals were to analyse the elements of the notions of language and categorize them according to the metaphors found in the discourse. The empirical data was taken from comments under three news (three for each country), approximately 1640 comments were collected and the ones that contained metaphorical representations of language were analysed, 257 in total. The results show eight different notions of language, which are called: prescriptivist / authoritarian, instrumentalist, ethnolinguistic, communicative, essentialist, „personal identity“, elitist and constructivist. The last three notions are specific for only one of the environments and are discussed in greater detail. From the users’ perspective, the difference between the notions is based on several elements, most importantly: the place of language in society (what is the relationship to standard and non-standard varieties) perception of change and function and functionality of language. The results also show that notions of ‘pure language’ are connected not only to the ethnolinguistic notion of language (language as a part of the identity, change is understood as decay), but also with other varieties of language are connected with different (even opposing) ideals and practical concerns (language as a neutral tool of communication, as a separate organism, substance etc.), and, finally, those notions of language, where the differentiation between the varieties of language is not important, is only connected with the communicative function (communicative notion of language – language is communication). Speaking about language ideologies in general, results show that there are of language in which standard language ideology (according to Milroy 2001) is negatively valued.
Keywords: notions of language; online user comments; cognitive metaphors; cultural models; language ideologies; sociolinguistics